ANALYSIS OF TUBERCULOSIS TREATMENT SUITABILITY AND THE DRUG SUPERVISOR’S ROLE IN A COMMUNITY HEALTH CENTER IN PADEMANGAN SUBDISTRICT, NORTH JAKARTA - FEBRIONY, CITRA; PURWANTYASTUTI; RASMIN, MEANALDI; SOETIKNO, VIVIAN (International Journal of Applied Pharmaceutics, 2019)
Objective: Appropriate tuberculosis (TB) treatment guidelines are one of the many factors that influence the success of TB treatment. The patient’s drug supervisor is a functional role that is part of the directly observed treatment short course, a program to support the success of TB treatment. The aim of this study was to analyze the TB treatment suitability in a community health center and the benefit of treatment compliance supervision by the patient’s designated drug supervisor. Methods: We conducted a cross-sectional study in the Community Health Center of Pademangan subdistrict, North Jakarta, involving 205 subjects to analyze appropriate fixed-dose combination (FDC) anti-TB drug administration and an experimental study involving 23 control group TB patients and 23 intervention group TB patients to assess the benefit of supervision by each patient’s drug supervisor. Results: The association of FDC anti-TB drug side effects with the success of TB treatment was not statistically significant (p=0.173). There was an increase in drug supervisor knowledge of 8.6% in the intervention group and 13% in the control group. There was no statistically significant association between the knowledge of the drug supervisor and the 2nd month (p=0.575) and the 6th month of sputum treatment. Conclusion: Minor side effects of FDC anti-TB drug did not affect the success of TB treatment; therefore, treatment was continued if these adverse events occurred. There were no correlations between the drug supervisor knowledge level with medication compliance or with sputum conversion (months 2 and 6).